Human Development and Its Effects on Economic Growth and Development - Appiah, Michael; Amoasi, Richard; Frowne, Doreen Idan (Universitas Prasetiya Mulya, 2019)
The focus of the current study is to empirically examine the impact of Human Development on Economic Growth and Development in African countries, between 1990 and 2015. The key findings and results of the study suggested the existence of a positive and significant impact of human development on economic growth and development in Africa. The study employed Human Development Index as the main variable of interest with GDP considered as the dependent variable with inflation, capital, investment and labour as control variables. The study also came out with the findings that Labour and foreign aid also have a positive and significant relationship with growth as recorded by most researchers. It was recommended that more efforts should be placed on developing the human capacities in all areas.